TREN SOSIO-SUFISTIK DALAM TAFSIR JAWA: (Pemikiran dan Tren Tafsir Kiai Saleh Darat Semarang Dalam Kitab Faidl al-Rahman) - Wahab, Abdul (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2020)
Tafsir Faidl al-Rahma>n is a work of tafsir written by one of the archipelago scholars of the namely Kiai Saleh Darat, this tafsir is written using the Java language and Arabic pegon script, the goal, in addition as a mean of communication between writers and readers who are Javanese, Java language and the writing of this pegon is also a symbol of resistance against the invaders. The method used in Tafsir Faidl-al-Rahma>n is the analytical method (tah}li>li>) with the Sufistic genre or isya>ri, the Sufistic genre promoted by Kiai Saleh is very unique, because Kiai Saleh is very firm in holding principle, ie incompatibility with the Sufistic genre which is symbolic, even the genre of Sufistik that is carried by Kiai Saleh can be said as "socio-sufistik" genre, which means the nuances of sufistik contained in his tafsir always associated with the dynamics of social life that is pervasive and always applicable in the midst of social life in order to form moral religious society towards the realization of the whole human being (insa>n ka>mil). Interpreted verses are presented with a comprehensive meaning and then are explained by using the meaning of isya>ri contained in certain verses. Tradition history and also interteks also colored nuances in the interpretation of one of the scholars of this very inspiring archipelago. By using the hermeneutic approach, this research was conducted to reveal deeper thoughts and genres of Kiai Saleh's commentary in the book Faidl al-Rahma>n. A very proud and extraordinary academic work.